Health Promotion Media Exposure and Student Compliance Toward Smoke-Free School Regulation In Sleman Yogyakarta - Heni Trisnowati; Rini Dwi Susanti; Nuraini Nuraini (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
The number of adolescent smokers in Indonesia are increasing with the highest prevalence on age 15-19. Implementation of smoke-free schools (SFS) aims to reduce adolescent smokers and protect school residents from cigarette smoke exposure. Public Senior High School 1 Cangkringan, Sleman has declared a SFS since 2019 by providing health promotion media such as posters and stickers in the school area. This study describes the implementation of SFS and to determine the relationship between health promotion media exposure and student compliance toward SFS regulations using quantitative methods with a cross-sectional design. Data collection was carried out through observation with checklists and online surveys with a google form. Sampling using accidental sampling method to 155 respondents and data analysis using SPSS version 17 with Chi-Square test. All respondents stated that the implementation of SFS is good and the results of observations showed that the input, process, and output indicators of SFS implementation had been fulfilled. Most of the students (83.2%) were exposed to high-level health promotion and 98,1% students obeyed the SFS regulations, There was a relationship between exposure to health promotion media in the form of posters with student compliance with SFS regulations ρ value ≤ α (0.004 ≤ 0.05). In conclusion, the high exposure to health promotion media has implications for the high compliance of students to SFS regulations.